Magnetically Assembled SERS Substrates Composed of Iron-Silver Nanoparticles Obtained by Laser Ablation in Liquid - Scaramuzza, Stefano (2017)
The widespread application of surface-enhanced Raman scattering (SERS) would benefit from simple and scalable self-assembly procedures for the realization of plasmonic arrays with a high density of electromagnetic hot-spots. To this aim, the exploitation of iron-doped silver nanoparticles (NPs) synthesized by laser ablation of a bulk bimetallic iron–silver target immersed in ethanol is described. The use of laser ablation in liquid is key to achieving bimetallic NPs in one step with a clean surface available for functionalization with the desired thiolated molecules. These iron–silver NPs show SERS performances, a ready response to external magnetic fields and complete flexibility in surface coating. All these characteristics were used for the magnetic assembly of plasmonic arrays which served as SERS substrates for the identification of molecules of analytical interest. The magnetic assembly of NPs allowed a 28-fold increase in the SERS signal of analytes compared to not-assembled NPs. The versatility of substrate preparation and the SERS performances were investigated as a function of NPs surface coating among different thiolated ligands. These results show a simple procedure to obtain magnetically assembled regenerable plasmonic arrays for repeated SERS investigation of different samples, and it can be of inspiration for the realization of other self-assembled and reconfigurable magnetic–plasmonic devices.